2022
DOI: 10.1038/s41413-022-00188-y
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord injury reprograms muscle fibroadipogenic progenitors to form heterotopic bones within muscles

Abstract: The cells of origin of neurogenic heterotopic ossifications (NHOs), which develop frequently in the periarticular muscles following spinal cord injuries (SCIs) and traumatic brain injuries, remain unclear because skeletal muscle harbors two progenitor cell populations: satellite cells (SCs), which are myogenic, and fibroadipogenic progenitors (FAPs), which are mesenchymal. Lineage-tracing experiments using the Cre recombinase/LoxP system were performed in two mouse strains with the fluorescent protein ZsGreen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…In addition, while our mouse model of NHO recapitulates many features of NHO observed in patients with SCI, 12 a limitation of our model is that it does not recapitulate the endochondral phase observed in human NHO. We have previously established that NHO forms in our mouse model via intramembranous ossification, 14 , 15 which could also potentially explain our contrasting results with those in non-neurologic models of traumatic HO.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, while our mouse model of NHO recapitulates many features of NHO observed in patients with SCI, 12 a limitation of our model is that it does not recapitulate the endochondral phase observed in human NHO. We have previously established that NHO forms in our mouse model via intramembranous ossification, 14 , 15 which could also potentially explain our contrasting results with those in non-neurologic models of traumatic HO.…”
Section: Discussionmentioning
confidence: 85%
“…(59,60) It must be noted, however, that supraphysiological BMP-2 overexpression is nonphysiological, very osteogenic, and this does not represent a physiologically relevant model of SCI-induced NHO. (12,19) Furthermore, LPS-activated mouse macrophages express Acvr1 and Acvr2a mRNA (see www.biogps.org), which encode BMP receptors, and this may alter their subsequent response to LPS once stimulated by supraphysiological concentrations of BMP-2. Therefore, it is difficult to extrapolate from these studies in which BMP-2 is artificially overexpressed, the relevance to SCI-induced NHO that does not involve supraphysiological expression of BMP-2 in the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…(17,18) Mineralized foci can be detected in injured muscles from as early as 4 days post-surgery and develop over a period of 2 weeks into mature mineralized heterotopic bone nodules (formed via intramembranous ossification) with osterix+/osteocalcin+ osteoblast-like cells present by 21 days post-surgery. (17,19) Using this model, we have shown that monocytes/macrophages infiltrating the injured muscle are critical in promoting NHO development, (17) whereas granulocytes and lymphocytes are dispensable. (20,21) Further studies revealed that SCI drives a prolonged inflammatory response in injured muscles (22) with elevated and persistent expression of the inflammatory cytokines oncostatin M (OSM) and interleukin-1 (IL-1), which both promote NHO development.…”
Section: Introductionmentioning
confidence: 97%
“…This leads to the proliferation of fibroadipogenic progenitors (FAPs) within the injured periarticular muscles and their subsequent osteogenic differentiation. FAPs are derived from mesenchyme [ 9 ] and can differentiate into chondrocytes, osteoblasts, or adipocytes [ 33 ]. Hypoxia appears to be one of the main factors contributing to a conducive environment.…”
Section: Reviewmentioning
confidence: 99%
“…NHO has an incidence of 10-23% in patients with TBIs and 10%-53% in patients with SCIs [ 9 ]. Clinical risk factors attributed to NHO include severity of CNS injury, spasticity, pressure ulcers, systemic infection, and prolonged immobilization [ 10 ].…”
Section: Introductionmentioning
confidence: 99%